Africa-Europe Research and Innovation Cooperation Global Challenges, Bi-regional Responses (Springer International Publishing, 2018)
This book is open access under a CC BY 4.0 license. This edited volume is concerned with the evolution and achievements of cooperation in research and innovation between Africa and Europe, and points to the need for more diversified funding and finance mechanisms, and for novel models of collaboration to attract new actors and innovative ideas. It reflects on the political, economic, diplomatic and scientific rationale for cooperation, while also examining practical developments, illustrated with examples, in the fields of food security, health, and climate change. The need to mobilise scientific knowledge and to ensure equality and fairness in the cooperation are recurrent themes. Africa-Europe Cooperation in Research and Innovation is essential reading for policy makers and researchers in international relations and science diplomacy. Andrew Cherry is Senior Scientific Officer at the Association of Commonwealth Universities. He currently manages projects on fostering international collaboration in research and innovation, and has coordinated both the CAAST-Net and CAAST-Net Plus projects since 2008. James Haselip is Senior Researcher at the UNEP DTU Partnership in Copenhagen. He works on the transfer and diffusion of low carbon and cleaner energy technologies in non-OECD markets. Gerard Ralphs is Programme Manager and Policy Analyst at the Human Sciences Research Council of South Africa. He works on South Africa's national surveys of R&D and innovation performance. Isabella E. Wagner is Researcher and Project Coordinator at the Centre for Social Innovation, Austria. She is conducting projects on international cooperation in research and innovation with one specific focus on Africa.